Oziella sibirica (Acari: Eriophyoidea: Phytoptidae), a new eriophyoid mite species described using confocal microscopy, COI barcoding and 3D surface reconstruction - Chetverikov, Philipp E.; Beaulieu, Frédéric; Cvrković, Tatjana; Vidović, Biljana; Petanović, Radmila U. (Zootaxa, 2012)
Oziella sibirica sp. nov., collected from sedges (Cyperaceae: Carex macroura) in Siberia, Russia, is herein describedbased on the external morphology of all active instars using primarily conventional phase contrast microscopy, andon the female internal genitalia and prodorsal shield design using confocal laser scanning microscopy (CLSM)imaging and a 3D modelling technique. A partial mitochondrial COI gene sequence of O. sibirica sp. nov. is alsoprovided, through GenBank, and this represents the first published record of any gene sequence data for the familyPhytoptidae. We present remarks on the phylogenetic significance of the position of setae 3a in immature instars oferiophyoids and on the ontogenic variability of the empodium morphology of O. sibirica sp. nov. Using this speciesas a model, we propose a method for describing the internal genitalia of eriophyoids based on CLSM. We advocatethe use of CLSM imaging as a new, relatively simple technique for observing and describing the internal genitalia oferiophyoids, as these largely unexplored genitalic structures may provide phylogenetically meaningful informationfor improving the classification of this poorly understood group of mites. In addition, CLSM may complementconventional light microscopy techniques in facilitating the interpretation of external structures such as body ornamentation or chaetotaxy.